Fixed Point Theorems for Ciric's and Generalized Contractions in b-Metric Spaces - Muhammad Sarwar; Mujeeb Ur Rahman (International Journal of Analysis and Applications, 2015)
In this article we obtained b-metric variant of common fixed point results for Ciric's and generalized contractions. We have also proved some fixed point results for rational contractive type conditions in the context of b-metric space. A particular example is also given in the support of our established result regarding Ciric's type contraction.